The Role of Regional Contrast Changes and Asymmetry in Facial Attractiveness Related to Cosmetic Use - Killian, Amanda C.; Mitra, Sinjini; Peissig, Jessie J. (Frontiers in Psychology, 2018)
This study collected behavioral data for testing how regional contrast changes due to the addition of cosmetics would affect attractiveness ratings. In addition, we used an established model of asymmetry to look for a correlation between changes in attractiveness related to the application of cosmetics to specific regions of the face and changes in symmetry. Using this asymmetry model we compared female faces with and without makeup. Specifically, we used a highly controlled set of greyscale faces in which makeup application was standardized to explore these issues from a perceptual perspective. The human data showed that adding upper eye makeup significantly increased attractiveness ratings. In contrast, increases in contrast to the lower eyes and lips did not lead to increases in attractiveness ratings; application of cosmetics to the lower eyes led to a significant decrease in attractiveness. We found that for the makeup condition that led to increased attractiveness, asymmetry did not change significantly when makeup was applied to the female faces. This suggests a role for mechanisms other than symmetry related to increases in attractiveness related to makeup use in females.